Evaluation of mental foramen and accessory mental foramen in retrospective magnetic resonance images - BORAHAN, MEHMET OĞUZ (My University, 2023)
Objective: This retrospective study aims to assess the morphologic characteristics of mental foramen (MF) and the incidence of accessory mental foramina (AMF) by using magnetic resonance imaging (MRI). Material and Method: 3.0-Tesla Turbo Spin Echo (3T TSE) MRI sequences of 40 patients were included in the study group. MF was detected in axial sections bilaterally, and the diameter of MF was measured. Also, the presence of AMF was recorded. Data were statistically analyzed (p<0.05). Results: A total of 80 semi-mandibles (40 right, 40 left) were evaluated in the study. The incidence of AMF was found as 6.3%. The mean diameter of MF was statistically nonsignificant regarding age groups, gender, and the side of the mandible (p>0.05). Conclusion: MRI is a promising imaging method for the evaluation of morphological features of MF and its anatomical variations (AMF). MRI should be recommended when CBCT represents an unclear appearance of MF.

Amaç: Bu çalışmanın amacı, Manyetik Rezonans Görüntüleme (MRG) yöntemi kullanarak mental foramenin (MF) morfolojik özelliklerini ve aksesuar mental foramen (AMF) görülme sıklığını saptamaktır. Gereç ve Yöntemler: 40 hastaya ait 3.0-Tesla Turbo Spin Eko (3T TSE) MRG görüntüleri çalışmaya dahil edilmiştir. MF bilateral olarak aksiyel kesitlerde tespit edilerek çapı ölçülmüştür. Ayrıca, AMF varlığı kaydedilmiştir. Veriler istatistiksel olarak analiz edilmiştir (p<0.05). Bulgular: Toplam 80 yarım mandibula (40 sağ, 40 sol) değerlendirilmiştir. AMF sıklığı %6.3 olarak tespit edilmiştir. MF çapı yaş grupları, cinsiyet ve mandibulanın sağ veya sol tarafında olmasına göre değerlendirildiğinde anlamlı bir fark elde edilememiştir (p>0.05). Sonuç: MRG, MF morfolojisini değerlendirmede ve anatomik varyasyonlarının (AMF) görüntülenmesinde gelecek vaat eden bir yöntemdir. Konik ışınlı bilgisayarlı tomografinin MF görüntülemede yetersiz kaldığı durumlarda MRG önerilebilir.
Mental foramen ve aksesuar mental foramenin manyetik rezonans görüntüleme ile retrospektif değerlendirilmesi
Keywords: Accessory mental foramen; Magnetic resonance imaging; Mental foramen; Neurovascular imaging; Aksesuar mental foramen; Manyetik rezonans görüntüleme; Nörovasküler görüntüleme